ANALISIS KEMAMPUAN MATEMATIKA DASAR SISWA KELAS V SEKOLAH DASAR : Analisis Kemampuan Matematika Dasar Siswa Kelas V Sekolah Dasar - Asalamah, Aisah; Mumpuni, Atikah; Nurpratiwiningsih, Laelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the basic mathematics skills of fifth grade students and explore the obstacles faced in improving them. The approach used is descriptive qualitative with five students as subjects who have scores below the Minimum Completion Criteria (KKM). Data collection techniques were carried out through interviews, observations, and documentation. The results of the study indicate that students' basic mathematics skills are still low, especially in understanding the concept of numbers, arithmetic operations, and their application in contextual problems. Some of the obstacles found include low learning motivation, difficulty in understanding the material, lack of home tutoring, and learning methods that are not fully in accordance with students' needs. These findings indicate the need for more varied learning strategies and support from the students' environment to improve basic mathematics skills optimally. Keywords: Basic Mathematics Ability, Obstacles, Grade V Students